Design-based educational platform for computational thinking with automated grading - Shandilya, Sanchita (2015)
The young generation of today are commonly referred to as “digital natives”, given their unprecedented fluency with technology. However, digital fluency is not just the ability to chat, browse and interact with digital media but also the ability to design and create this new media. Programming and computational thinking form the basis of this creation process. Learning computational thinking can expand the ways in which this generation can express themselves with a computer. Furthermore, computational thinking imparts important skills in problem solving, systematic thinking and design that have benefits far beyond the programming domains. Therefore, it is important to introduce children to these concepts at a young age in order to prepare them for an increasingly complex, digitally driven world. The aim of this project was to develop an educational platform that introduces children to computational thinking using a design based pedagogy. The result is MazeWorks—a platform that allows children to create their own mazes, and solve these mazes using code scripts generated by code blocks. To facilitate learning, MazeWorks includes an intelligent automated grading framework that provides instant feedback to children. Also, it dynamically calculates the most optimal solution to a maze and compares the player’s solution to the ideal solution. This report discusses the design principles and technologies that contributed to the development of MazeWorks. The author also explores the challenges associated with designing an effective educational platform for children, and recommends improvements for future development iterations of MazeWorks.